2006
DOI: 10.1186/1744-8069-2-20
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of Metabotropic Glutamate Receptor 2/3 Expression by the NF-κB Pathway in Primary Dorsal Root Ganglia Neurons: A Possible Mechanism for the Analgesic Effect of L-Acetylcarnitine

Abstract: L-acetylcarnitine (LAC), a drug utilized for the treatment of neuropathic pain in humans, has been shown to induce analgesia in rodents by up-regulating the expression of metabotropic glutamate receptor 2 (mGlu2) in dorsal root ganglia (DRG). We now report that LAC-induced upregulation of mGlu2 expression in DRG cultures involves transcriptional activation mediated by nuclear factor-kappaB (NF-κB). A single application of LAC (250 μM) to DRG cultures induced a transient increase in mGlu2 mRNA, which was observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 39 publications
1
69
1
2
Order By: Relevance
“…Our results are in contrast to studies that demonstrate neuroprotective and pro-regenerative ALCAR effects in other nerve injury models (Fernandez et al, 1991;Pacifici et al, 1992;Lowitt et al, 1995;Sima et al, 1996Sima et al, , 2005Hart et al, 2002Hart et al, , 2004aHart et al, , 2004bDeGrandis and Minardi, 2002;Wilson et al, 2003Wilson et al, , 2007Chiechio et al, 2006;Youle et al, 2007). Pisano et al (2003) showed that a prophylactic ALCAR treatment protocol prevented the decrease in the sensory nerve conduction velocity (SNCV) seen after paclitaxel and cisplatin.…”
Section: Alcar and The Paclitaxel-evoked Degeneration Of Ienfscontrasting
confidence: 55%
See 2 more Smart Citations
“…Our results are in contrast to studies that demonstrate neuroprotective and pro-regenerative ALCAR effects in other nerve injury models (Fernandez et al, 1991;Pacifici et al, 1992;Lowitt et al, 1995;Sima et al, 1996Sima et al, , 2005Hart et al, 2002Hart et al, , 2004aHart et al, , 2004bDeGrandis and Minardi, 2002;Wilson et al, 2003Wilson et al, , 2007Chiechio et al, 2006;Youle et al, 2007). Pisano et al (2003) showed that a prophylactic ALCAR treatment protocol prevented the decrease in the sensory nerve conduction velocity (SNCV) seen after paclitaxel and cisplatin.…”
Section: Alcar and The Paclitaxel-evoked Degeneration Of Ienfscontrasting
confidence: 55%
“…2006;Chiechio et al, 2006). It seems unlikely that such mechanisms could account for ALCAR's ability to completely prevent paclitaxel-evoked neuropathic pain.…”
Section: The Analgesic Effect Of the Prophylactic Alcar Dosing Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…To confirm more specifically that our effects were not due to other potential signaling pathways linked to IL1␤/IL1r1, we also performed control experiments to assess whether IL1␤ may be mediating its effects on ASIC3 expression via the NFB pathway (O'Neill and Greene, 1998). To this end, we treated afferents retrogradely labeled by FG from the muscles with IL1␤ and the NFB inhibitor CAPE (Chiechio et al, 2006) and found that CAPE treatment had no effect on IL1␤-mediated ASIC3 upregulation (IL1␤ ϩ CAPE: 73.03 Ϯ 4.92 fold, p ϭ 0.343 vs untreated; CAPE only: 23.77 Ϯ 4.85, p ϭ 0.041). Using MatInspector software (Genomatix), we determined that JNKmediated ASIC3 expression is likely due to the fact that ASIC3 has multiple AP1/Jun transcription factor-binding sites in its upstream promoter region (Fig.…”
Section: Activated C-jun N-terminal Kinase Signaling Promotes Asic3 Ementioning
confidence: 99%
“…Recent evidence suggests that the acetylating agent L-acetylcarnitine (LAC), a drug marketed for the treatment of neuropathic pain (9), causes analgesia increasing type 2 metabotropic glutamate (mGlu2) expression via an epigenetic mechanism shared by HDAC inhibitors (10)(11)(12). mGlu2 and its cognate receptor, mGlu3, are coupled to Gi/Go proteins and are preferentially (albeit not exclusively) localized in the preterminal region of axons, where they negatively modulate neurotransmitter release (13).…”
mentioning
confidence: 99%